Improving Psychosocial Status And Nutritional Status Through Nursing And Nutritional Health Interventions In Kampung Baru Kuala Lumpur - Tutik Agustini; Yusriani Yusriani; Muhammad Khidri Alwi; Alika Nurul Hidayah; Syabania Hasana Muhammad (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Students who attend informal education centers generally come from families with low socioeconomic backgrounds, which makes them vulnerable to psychosocial problems such as stress, anxiety, and low self-confidence. Furthermore, inadequate nutritional intake risks leading to nutritional status issues such as chronic energy deficiency (CED) and underweight. These psychosocial and nutritional issues can directly impact children's health, development, and academic achievement. Therefore, integrated efforts are needed to improve their psychological well-being and nutritional status. The solutions offered in this community service activity are community nursing interventions and nutritional health interventions. The nursing approach is implemented to support students' mental health through activities such as group counseling, social skills training, and strengthening peer support. Meanwhile, the nutritional health approach is implemented through balanced nutrition education, training in preparing menus based on local foods, and providing nutritious supplementary feeding (PMT). A participatory approach was used, including educational sessions, practical demonstrations, and assessments through pre- and post-tests. The results showed significant improvements, with knowledge increasing from 35% to 95%, positive attitudes from 35% to 85%, and practical skills from 27% to 90%. Outputs included scientific publications, educational videos, posters, and enhanced cadre competencies. The program provided sustainable benefits by empowering students to promote health within their community and contributed to university performance indicators through active involvement of students and faculty. Overall, the program successfully achieved its objectives, with recommendations for continued support and collaboration to sustain and expand its impact.